#IamaRefugee: Social Media Resistance to Trump's 'Muslim Ban'. (28th February 2021) - Estrada, Emily P; Anderson, Alecia D; Brown, Angela
Abstract: Immediately after newly inaugurated President Trump issued Executive Order 13769 in 2017, commonly referred to as the 'Muslim ban', people around the world engaged in widespread resistance in a variety of ways, including through a relatively new forum: social media. While scholars have examined counterframing and symbolic boundary-work in resistance movements, little is known about impact social media platforms may have on these narratives. Accordingly, in this article, we explore how actors engage in boundary-work and counterframing through the use of social media. Using Twitter posts containing '#IamaRefugee' as our data, we find that activists engaged in different dimensions of boundary-work in opposition to Trump's ban including creating boundaries between the immoral 'them' and moral 'us'; challenging the boundaries between supposedly threatening refugees and the dominant group; and strengthening the bond of those in opposition to Trump's policies and rhetoric by reinforcing the messages of solidarity. We argue that this boundary-work culminated in direct calls for mobilization. The implications of our findings are meaningful to scholarship on refugee studies, social movements, and framing and to those interested in opposing problematic elite framing.